Perspective of people with epilepsy about Epilepsy (Bangladesh Journal of Medical Science, 2021)
Objective: This study aims to define epilepsy patient perspective about epilepsy.Material & methods:Phenomenological hermeneutic approach is used by emphasizing on van Manon (2001) method. In this study participants have chosen by targeted sampling. Semi structured interviews as well as observation have deployed for data collectionResults: Patient’s perspective explored by main four themes including: dumb concept, destructive agent of present and future’s life, the cause of social isolation and divine punishment.Conclusion:Epilepsy is a disorder which is bounded by ambiguity and unawareness among patients and societies. The disease also known by them as an incurable and destructive disease, present and future’s life destructive element, the cause of social isolation, divine punishment and atonement for sins.Bangladesh Journal of Medical Science Vol.20(2) 2021 p.374-378